Framework para diagnóstico e gestão de ambientes de Energy Cloud - Schaefer, Jones Luís (2022)
The energy sector is going through a transition process regarding the generation, distribution, storage and use of energy. This transition of energy systems has occurred through the evolution of these systems that were previously characterized as being totally centralized, passing through a decentralized modality, and with the technological evolutionary directions pointing to a completely flexible and dynamic modality. This flexible and dynamic modality becomes known in the literature through terms such as Energy Cloud, Energy 4.0, and Smart Energy. The insertion of this modality is driven by three vectors: the distributed generation of energy from renewable sources, electric vehicles, and energy storage systems. Considering this evolution of energy systems, it is relevant to carry out research related to management on the development and implementation of business environments based on the Energy Cloud concept. Therefore, this research had as general objective to propose a framework for integrated management and assessment of technical, economic, financial, environmental and organizational aspects aiming at the development and implementation of Energy Cloud environments. To achieve this objective, the research was developed through five scientific articles designed to study specific points that contribute to achieving the general objective. Considering the three vectors that drive the evolution of Energy Cloud, first aspects that characterize the ecosystem were studied, such as the players, elements, activities and basic requirements of Energy Cloud as a business modality. In a second moment, the performance objectives to be pursued by companies included in the Energy Cloud were researched, as well as what are the critical success factors that can be considered as limiting the business. Afterwards, the scientific subsidies obtained were structured in a framework for diagnosis and management of Energy Cloud Communities environments, exemplifying the use of this framework to understand the specificities necessary for organizations that operate in this type of business. Methodologically, the research was developed based on bibliographic and documental research, survey with specialists in related areas, multicriteria decision support methods, and algorithms for knowledge construction. This research seeks to contribute through the definition of the ecosystem of Energy Cloud business environments and the elaboration of a management framework where the variables are structured to assist in the management and decisionmaking for organizations operating in the different areas that make up the Energy Cloud. This framework provides a multilevel view of variables, aggregating different multicriteria analysis methods and enabling a comprehensive view of the objectives, constraints, challenges and opportunities in the Energy Cloud Communities environment.